Targeted Exon Skipping to Correct Exon Duplications in the Dystrophin Gene - Kane L Greer; Hanns Lochmüller; Kevin Flanigan; Susan Fletcher; Steve D Wilton (Elsevier, 2014)
Duchenne muscular dystrophy is a severe muscle-wasting disease caused by mutations in the dystrophin gene that ablate functional protein expression. Although exonic deletions are the most common Duchenne muscular dystrophy lesion, duplications account for 10-15% of reported disease-causing mutations, and exon 2 is the most commonly duplicated exon. Here, we describe the in vitro evaluation of phosphorodiamidate morpholino oligomers coupled to a cell-penetrating peptide and 2'-O-methyl phosphorothioate oligonucleotides, using three distinct strategies to reframe the dystrophin transcript in patient cells carrying an exon 2 duplication. Differences in exon-skipping efficiencies in vitro were observed between oligomer analogues of the same sequence, with the phosphorodiamidate morpholino oligomer coupled to a cell-penetrating peptide proving the most effective. Differences in exon 2 excision efficiency between normal and exon 2 duplication cells, were apparent, indicating that exon context influences oligomer-induced splice switching. Skipping of a single copy of exon 2 was induced in the cells carrying an exon 2 duplication, the simplest strategy to restore the reading frame and generate a normal dystrophin transcript. In contrast, multiexon skipping of exons 2-7 to generate a Becker muscular dystrophy-like dystrophin transcript was more challenging and could only be induced efficiently with the phosphorodiamidate morpholino oligomer chemistry.